Support for the coevolution of Neoparamoeba and their endosymbionts, Perkinsela amoebae-like organisms - Young, Neil D; Dyková, Iva; Crosbie, Philip B B; Wolf, Matthias; Morrison, Richard N; Bridle, Andrew R; Nowak, Barbara F (European journal of protistology, 2014)
Some of the species from the genus Neoparamoeba, for example N. perurans have been shown to be pathogenic to aquatic animals and thus have economic significance. They all contain endosymbiont, Perkinsela amoebae like organisms (PLOs). In this study we investigated phylogenetic ambiguities within the Neoparamoeba taxonomy and phylogenetic congruence between PLOs and their host Neoparamoeba to confirm the existence of a single ancient infection/colonisation that led to cospeciation between all PLOs and their host Neoparamoeba. DNA was extracted and rRNA genes from host amoeba and endosymbiont were amplified using PCR. Uncertainties in the Neoparamoeba phylogeny were initially resolved by a secondary phylogenetic marker, the internal transcribed spacer 2 (ITS2). The secondary structure of ITS2 was reconstructed for Neoparamoeba. The ITS2 was phylogenetically informative, separating N. pemaquidensis and N. aestuarina into distinct monophyletic clades and designating N. perurans as the most phylogenetically divergent Neoparamoeba species. The new phylogenetic data were used to verify the tree topologies used in cophylogenetic analyses that revealed strict phylogenetic congruence between endosymbiotic PLOs with their host Neoparamoeba. Strict congruence in the phylogeny of all PLOs and their host Neoparamoeba was demonstrated implying that PLOs are transmitted vertically from parent to daughter cell.
Keywords: symbióza; ITS2; Phylogeny; Amoebozoa; Perkinsela; Kinetoplastida; DNA, Ribosomal Spacer; Molecular Sequence Data; molekulární sekvence - údaje; Symbiosis; Endosymbiont; RNA ribozomální 18S; Neoparamoeba; fylogeneze; mezerníky ribozomální DNA; RNA, Ribosomal, 18S